The Development of Local Capital Markets : Rationale and Challenges - Laeven, Luc (IMF Working Papers; Working Paper ;, 2014)
Capital markets can improve risk sharing and the efficiency with which capital is allocated to the real economy, boosting economic growth and welfare. However, despite these potential benefits, not all countries have well developed capital markets. Moreover, government-led initiatives to develop local capital markets have had mixed success. This paper reviews the literature on the benefits and costs of developing local capital markets, and describes the challenges faced in the development of such markets. The paper concludes with a set of policy recommendations emerging from this literature.